Hubungan Self-Control terhadap Fear of Missing Out (Fomo) pada Mahasiswa - Rachel Chintya Innayah; Wilta Amanda Caramon; Annisa Khairani Ritonga; Beny Rahim; Jelpa Periantalo; Muhammad Ilham; Dinda Agraiza (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The development of information technology and social media has made it easier for university students to access information and maintain social interactions. However, excessive social media use may lead to the phenomenon of Fear of Missing Out (FoMO), a feeling of anxiety when individuals believe they are missing out on experiences, activities, or information enjoyed by others. One psychological factor presumed to reduce FoMO is self-control. This study aimed to examine the relationship between self-control and Fear of Missing Out (FoMO) among university students. This study employed a quantitative method with a correlational design. The participants consisted of 55 active university students aged 18–23 years who met the research criteria. Data were collected online through Google Forms using self-control and FoMO scales developed based on relevant theories. Data analysis was conducted using JASP through assumption tests, including normality and linearity tests. The normality test results showed that the self-control variable had a significance value of 0.435 and the FoMO variable had a significance value of 0.100 (p > 0.05), indicating that both variables were normally distributed. The linearity test results indicated a linear relationship between self-control and FoMO. Based on the findings and theoretical review, self-control functions as a psychological factor that helps individuals regulate social media use, manage the urge to remain constantly connected to digital social activities, and reduce the tendency to experience FoMO. The higher the level of self-control among students, the lower their tendency to experience Fear of Missing Out.